Lipid-based patterning of the immunological synapse. (17th November 2014) - Huse, Morgan
Abstract : The immunological synapse controls T-lymphocyte function by polarizing effector responses towards the antigen-presenting cell. In this review, I discuss the molecular pathways required for synapse assembly, focusing on the central roles played by lipid second-messenger signalling.